Imitation-mussel fluorescent silicon quantum dots for selective labeling and imaging of bacteria and biofilms - Lin, Jiayi; Xu, Linlin; Zheng, Yuling; Wu, Dalin; Yue, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Selective labeling of distinct bacteria and biofilm is poised for the fundamental understanding of bacterial activities, interactions and coupled phenomena occurring at the microscale. However, a simple and effective way to achieve selective bacterial labeling is still lacking. Herein, we reported a fluorescence probe with core-shell nanostructure that by coating polydopamine (PDA) on the surface of fluorescent silicon quantum dots (SiQDs@PDA). The surface of SiQDs@PDA was able to be functionalized by various molecules (thihydrethylamine hydrochloride, PEG, D-alanine, glucose amide) through different strategies (Michael addition, π-π interaction and ion-ion interaction). Importantly, the D-alanine (D-Ala) and gluconamide (Glc) functionalized SiQDs@PDA fluorescence probes are capable of selective labeling gram-positive and gram-negative bacteria as well as their biofilms. The excellent performance in universal functionalization, selective labeling and imaging of bacteria and their biofilms demonstrate that SiQDs@PDA is a promising fluorescence tool in microbe research.